Effect of γ-radiation-thermal coupling aging on the mechanical and radiolytic gas behavior of F2311 fluoroelastomer - ZHANG Yiqian; DOU Ruiyang; LIU Qiang; HUANG Wei; YAN Shunping; CHEN Hongbing (Fushe yanjiu yu fushe gongyi xuebao)
In national defense, aerospace, and nuclear power fields, the service environments of polymer materials in equipment are complex and necessitate high requirements for their radiation resistance and thermal stability. Therefore, studying the aging behavior of polymer materials in a coupled radiation-thermal environment is crucial. In this study, F2311 rubber material was subjected to aging tests in the temperature range of 36-70 °C, with an absorbed γ dose of 20 kGy, 100 kGy, 200 kGy. The effects of the coupled temperature and absorbed dose on the mechanical properties of F2311 were investigated. The gaseous products released by the F2311 material and their kinetic laws were determined using gas-phase infrared spectra. The experimental results showed that the mechanical properties of the F2311 elastomer deteriorated rapidly in the radiation-thermal environment. Radiolytic outgassing was inevitable, and the gaseous products included corrosive halogen hydrides. Gas-phase infrared spectroscopy can quickly identify and quantitatively analyze gaseous products to trace and supervise the service reliability of equipment. This study is expected to provide a basis for the study of coupled multifactor aging and compatibility of fluorine rubber.